MANIFESTASI GENDER DALAM STRUKTUR BUDAYA SPIRITUAL MASYARAKAT TOANI TOLOTANG - Nensilianti Nensilianti (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2012)
This study aimed to describe the status, roles, and gender inequality in the cultural structure of Toani Tolotang communities. Collecting  techniques of the data are through observation, indepth interviews and focus group discussions. The results showed: (1) the manifestation of the injustice caused by differences in the social strata (status quo) in society, namely: the impression of slavery, oppression and economic deprivation, restraint in decision-making, and differences in educational opportunities, (2) the manifestation of gender inequality caused by the beliefs of Toani Tolotang communities, namely: the feelings and individual decisions constrained by the status quo,  the limitation of movement and productivity for pregnant women, the over loyalty of wife to husband , the  unbalanced of sharing  roles and workloads between men and women, and lack of respect for the work of women.